Fatigue and creep-fatigue crack growth in alloy 709 at elevated temperatures. (2nd November 2019) - Shaber, N.; Stephens, R.; Ramirez, J.; Potirniche, G. P.; Taylor, M.; Charit, I.; Pugesek, H.
ABSTRACT: Fatigue crack growth (FCG) and creep-fatigue crack growth (CFCG) in austenitic stainless-steel Fe-25Ni-20Cr (Alloy 709) were measured experimentally and simulated using the finite element method. Temperature conditions investigated were 550°C, 600°C and 700°C, with load hold times of 0 s, 60 s and 600 s. Fracture surface was investigated using scanning electron microscopy and optical imaging. Experiments indicated that crack growth exhibits minimal sensitivity to the various loading conditions evaluated. At 600°C, crack growth rates were independent of hold time or loading frequency. At 700°C, there was a small increase in crack growth rate as a function of hold time, with a 600s hold time causing a factor of 2 increase in crack growth rate over FCG. Finite element simulations were performed to compute plasticity-induced crack closure in the presence of creep deformations at the crack tip. The simulations produced FCG and CFCG rates similar to the experimental results.